Nanoparticles, multifunctional hydrogel and their preparation and application
By introducing modified silsesquioxane nanoparticles into the hydrogel and grafting I2959 molecules, the problems of weak mechanical properties, high temperature sensitivity and poor optical properties of traditional hydrogel materials are solved, and a hydrogel material with high thermal insulation, fluorescence and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411835781.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Traditional hydrogel materials have shortcomings in mechanical strength, temperature sensitivity and optical properties, limiting their application range in certain specific fields.
Nanoparticles were prepared by modifying silsesquioxane (POSS) based on polyethylene glycol (PEG) segments and grafted 1 to 8 I2959 molecules at the end of the PEG segment to form a wide temperature strong fluorescent hydrogel.
The thermal insulation, fluorescence characteristics and mechanical properties of the hydrogel are significantly improved, so that it maintains a good thermal insulation effect in the range of -40℃ to 75℃, and exhibits significant bright blue fluorescence under 365 nm ultraviolet light excitation.
Smart Images

Figure CN119306951B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogels, and specifically relates to nanoparticles, multifunctional hydrogels and preparation and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Hydrogels have attracted extensive attention due to their unique physicochemical properties. Hydrogels are hydrophilic polymer networks that can absorb large amounts of water or biological fluids and maintain their three-dimensional structure. This material has shown great application potential in many fields such as drug delivery, tissue engineering, flexible electronic devices, and display technology.
[0004] Hydrogels that have high toughness, thermal insulation and fluorescent properties are of great significance for meeting the needs of modern complex applications. High toughness gives the material stability and reliability under mechanical stress, making it suitable for tissue engineering, flexible electronics and high-stress environments; thermal insulation enhances its adaptability under extreme temperature conditions, such as preventing heat loss in aerospace, cryogenic protection and energy storage equipment; and fluorescent properties provide it with real-time monitoring, visualization and intelligent response functions, which can be used in fields such as bioimaging, environmental detection and information encryption. This combination of multifunctional properties not only expands the application scenarios of hydrogels, but also significantly improves its energy utilization efficiency and long-term stability, meeting the urgent needs for multi-task comprehensive performance in fields such as smart medical care, energy management, and flexible devices.
[0005] However, traditional hydrogel materials have some inherent defects, such as low mechanical strength, temperature sensitivity and poor optical properties, which limit their application in certain specific fields.
[0006] In recent years, research on improving the toughness of hydrogels, enhancing their thermal insulation effects, and imparting fluorescent properties has made significant progress. 1. In terms of improving toughness, traditional hydrogels are prone to brittle fracture, which limits their application under mechanical stress conditions. In the research, double network hydrogels (DN hydrogels) are represented by the introduction of rigid and flexible networks to achieve mechanical performance optimization. For example, the high-strength double network design proposed by Hokkaido University in Japan is widely used; in addition, enhancing nonlinear deformation ability by introducing non-covalent interactions (such as hydrogen bonds, π-π stacking) is another important direction. There are also studies that improve toughness by modifying polymer chains, nanofillers (such as graphene oxide, MXene) or bionic designs (such as cartilage-like structures). 2. In terms of enhancing thermal insulation performance, some studies focus more on microporous structures and aerogel composites, and achieve efficient insulation by improving the thermal barrier capacity inside the material, such as the flexible aerogel hydrogel developed by the Lawrence Berkeley National Laboratory in the United States. Some studies combine the high water content of hydrogels with thermal resistance properties, and optimize thermal insulation properties by regulating porosity and water content. For example, the insulating hydrogels prepared by the Tsinghua University and Chinese Academy of Sciences teams using micro-nano bubble technology have outstanding performance in low-temperature protection and energy storage devices. 3. In terms of imparting fluorescent properties, some studies tend to introduce fluorescent molecules or quantum dots, such as the hydrogels containing fluorescent dyes developed by MIT for biosensing and visualization detection. Some studies combine functional polymers and rare earth elements to develop multifunctional hydrogels with both mechanical and optical properties. For example, the luminescent hydrogels prepared by the Peking University team through rare earth doping not only have long afterglow characteristics, but can also be used in flexible optical devices.
[0007] In general, the current research on hydrogel toughness, thermal insulation effect and fluorescence properties has entered the stage of multifunctional composite design. However, some market products use organic-inorganic composites to enhance the toughness and temperature adaptability of hydrogels. However, inorganic materials are prone to reduce the transparency of hydrogels during the composite process, and the compatibility of composite materials is poor, which ultimately leads to poor flexibility and durability. In addition, the preparation of composite materials is complex and costly, which poses obstacles to their application and promotion. Summary of the invention
[0008] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a nanoparticle, a multifunctional hydrogel, and their preparation and application. The nanoparticle is prepared based on polyethylene glycol (PEG) segment-modified silsesquioxane (POSS), and 1 to 8 I2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) molecules are grafted at the end of the PEG segment, and then a wide-temperature strong and tough fluorescent hydrogel is formed based on the nanoparticle. The present invention provides an innovative hydrogel material, which significantly improves the thermal insulation, fluorescent properties and mechanical properties of the hydrogel by introducing and synthesizing a new type of nanoparticle.
[0009] In order to achieve the above object, the technical solution of the present invention is:
[0010] In a first aspect, the present invention provides a nanoparticle, wherein the nanoparticle is composed of silsesquioxane and polyethylene glycol segments connected together, and the end of the polyethylene glycol segment is grafted with 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959).
[0011] Preferably, the molecular weight of polyethylene glycol is 200-3500, preferably 300-500.
[0012] The present invention uses silsesquioxane (POSS), while other common nanomaterials used for toughening, including silicon dioxide, carbon nanotubes, and nano-CaCO3, lack good compatibility and toughening effect with hydrogels in terms of particle size or do not have optical transparency.
[0013] The present invention uses polyethylene glycol (PEG), which has good biocompatibility, flexibility due to long chain segments, high activity of hydroxyl groups, and is easy to modify.
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned nanoparticles, comprising the following steps:
[0015] (1) Using silsesquioxane (POSS) and allyl-polyethylene glycol hydroxyl group (Allyl-PEG-OH) as raw materials, adding a catalyst to react, and obtaining a polyethylene glycol-modified silsesquioxane product (POSS-PEG-OH);
[0016] (2) The polyethylene glycol-modified silsesquioxane product (POSS-PEG-OH) and 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone (I2959-Br) are mixed, potassium carbonate and crown ether are added, and nanoparticles are obtained by extraction after reaction.
[0017] In one or more embodiments, in step (1), the ratio of silsesquioxane (POSS), allyl-PEG-OH and catalyst is (1-2 g): (5-6 g): (200-300 μL).
[0018] Preferably, the catalyst is a platinum catalyst, and the platinum catalyst is platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, and its concentration is 1-3% in xylene solution.
[0019] Preferably, in step (1), silsesquioxane (POSS) and allyl-PEG-OH are dissolved in an organic solvent. The organic solvent is anhydrous toluene. The mass volume ratio of silsesquioxane (POSS) to the organic solvent is 1: (50-100).
[0020] In one or more embodiments, in step (1), the catalyst is added to react by stirring at room temperature for 12-36 h, preferably 20-26 h.
[0021] In one or more embodiments, in step (1), after the catalyst is added and the reaction is completed, an organic solvent and activated carbon are added, stirred, filtered, the organic solvent is removed, and dried to obtain a polyethylene glycol-modified silsesquioxane product (POSS-PEG-OH). The organic solvent is CHCl3; the drying condition is 60-80°C for 12-24 hours.
[0022] In one or more embodiments, in step (2), the preparation method of 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone (I2959-Br) is as follows: 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) is dissolved in an organic solvent, heated, a catalyst and epibromohydrin (BCH) are added thereto for reaction, and unreacted epibromohydrin (BCH) and organic solvent are removed to obtain 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone (I2959-Br).
[0023] The organic solvent is anhydrous ethanol. The catalyst is boron trifluoride etherate. The heating temperature is 50-60°C. When adding the catalyst, it is added in two times; after adding the catalyst, epibromopropane (BCH) is slowly added dropwise. The reaction time is 1-5 hours, preferably 1-3 hours.
[0024] The ratio of the added amounts of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959), organic solvent, catalyst, and epibromohydrin (BCH) is (4-5 g):100 mL:(4-8 mL):(2-3 g).
[0025] In one or more embodiments, in step (2), the polyethylene glycol-modified silsesquioxane product (POSS-PEG-OH) is dissolved in an organic solvent, wherein the organic solvent is acetone, and the ratio of the polyethylene glycol-modified silsesquioxane product (POSS-PEG-OH) to acetone is (5-10 g):(40-80 mL).
[0026] The molar ratio of polyethylene glycol modified silsesquioxane product (POSS-PEG-OH) and 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone (I2959-Br) was 1:(1-8).
[0027] The ratio of 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone (I2959-Br), potassium carbonate and crown ether is (5-6 g):(1000-1200 mg):(500-600 mg).
[0028] The crown ether is 18-crown-6.
[0029] The reactive functional groups of POSS-PEG-OH and I2959 are both hydroxyl groups, which have low reactivity and cannot undergo complete substitution reactions. In order to improve the activity of I2959, the present invention uses epibromohydrin (BCH) to modify I2959, replaces the hydroxyl groups of I2959 with bromine groups, and obtains I2959-Br. Potassium carbonate provides an alkaline catalytic environment to promote the grafting reaction. 18-crown ether-6 is used as a surfactant to better disperse POSS-PEG-OH in the water phase and I2959-Br in the oil phase, and finally obtains POSS-PEG-I2959, wherein bromine is removed, so that the I2959 molecule is grafted at the end of the PEG segment.
[0030] In one or more embodiments, in step (2), the reaction temperature is 50-70° C., and the reaction time is 10-14 h.
[0031] In one or more embodiments, in step (2), the post-reaction extraction is to add an organic solvent for extraction, and remove the organic solvent to obtain nanoparticles.
[0032] In a third aspect, the present invention provides the use of the above-mentioned nanoparticles in hydrogels.
[0033] In a fourth aspect, the present invention provides a method for preparing a multifunctional hydrogel, comprising the following steps:
[0034] Acrylamide, water, a cross-linking agent and the above-mentioned nanoparticles are mixed and stirred to form a prepolymer solution, which is then cured by ultraviolet light to obtain a multifunctional hydrogel.
[0035] In one or more embodiments, the ratio of acrylamide, water, crosslinking agent and nanoparticles is (5-6 g):(5-6 g):(15-25 μL):0.01 mmol.
[0036] In one or more embodiments, the ultraviolet light is 350-380 nm, preferably 370 nm, and the curing time is 5-15 min.
[0037] In a fifth aspect, the present invention provides a multifunctional hydrogel prepared by the above method.
[0038] Under ultraviolet light excitation, the multifunctional hydrogel can emit bright blue fluorescence with a wavelength of 350-450 nm. The ultraviolet light excitation wavelength is 360-370 nm.
[0039] In a sixth aspect, the present invention provides applications of the multifunctional hydrogel in the fields of drug delivery, tissue engineering and display.
[0040] One or some of the above technical solutions have the following advantages or beneficial effects:
[0041] (1) The present invention provides a new type of nanoparticle, which is prepared based on polyethylene glycol (PEG) chain segment modified silsesquioxane (POSS). The rigid structure of POSS and the flexibility of PEG are used to give the hydrogel excellent thermal insulation properties, so that it maintains good thermal insulation effect in the range of -40℃ to 75℃, and the thermal conductivity is as low as 0.002 W / (m·K). In addition, 1 to 8 I2959 molecules are grafted at the end of the PEG chain segment. The carbonyl compound undergoes a proton transfer reaction with a large number of protons in the system, so that the hydrogel has fluorescent properties and exhibits a fluorescence emission of 425 nm wavelength under 365 nm ultraviolet light excitation. The synergistic effect of flexible long-chain PEG and rigid POSS, as well as the hydrogen bonding and physical entanglement effects between the PEG chain segment and the hydrogel molecules, significantly improves the toughness of the hydrogel, providing a new design idea and technical path for the development of multifunctional hydrogel materials.
[0042] (2) The present invention provides an innovative multifunctional hydrogel material. By introducing and synthesizing a new type of nanoparticle, the thermal insulation, fluorescence characteristics and mechanical properties of the hydrogel are significantly improved. The multifunctional hydrogel exhibits better flexibility and fracture resistance at -40℃~25℃, especially at low temperatures, as well as higher elongation at break and better flexibility. In addition, under heating conditions of 70℃, the surface temperature of the multifunctional hydrogel only rises to 40℃~50℃, respectively, and can remain stable within 10 minutes. It is obvious that it has excellent thermal insulation performance and can effectively slow down the transfer of heat. In addition, the multifunctional hydrogel prepared by grafting I2959 onto POSS-PEG nanoparticles can emit significant bright blue fluorescence under 365 nm ultraviolet light excitation, and with the increase of the grafting amount of I2959, the fluorescence intensity gradually increases, showing the adjustability of the fluorescence performance.
[0043] (3) Existing fluorescent hydrogels require the addition of luminescent materials such as fluorescein, carbon dots, and nanoclusters, or the addition of rare earth ions for coordination, or the increase of temperature to induce conjugation and produce fluorescence. However, in the present invention, no external fluorescent agent is required. Instead, the prepared G-1P 300 -1 and G-1P 300 -8 hydrogels can show obvious blue fluorescence, and with the increase of I2959 grafting amount, the fluorescence intensity gradually increases, showing the adjustability of fluorescence performance. In the present invention, hydrogels initiated by other initiators such as azobisisobutyronitrile (AIBN) and ammonium persulfate (APS) have no fluorescence.
[0044] (4) In the hydrogel material provided by the present invention, the eight side chain hydrogen bonding is used to enhance the mechanical properties. Specifically, POSS has eight side chains, which form a stable molecular network structure with the hydrogel matrix through hydrogen bonding, making the hydrogel o C ~75 o C) It still maintains good mechanical properties within a wide temperature range. This innovative side chain design provides temperature stability and durability that other flexible materials and hydrogels on the market do not have.
[0045] (5) In the hydrogel material provided by the present invention, π-π stacking and hydrogen bonding are used to improve toughness. Specifically, π-π stacking between I2959 molecules can be used to self-assemble between nanoparticles to generate strong non-covalent forces; and hydrogen bonds can be formed between ethylene glycol segments and acrylamide. The two effects work together to enable the hydrogel to maintain high toughness under repeated bending and stretching. This assembly method is different from traditional chemical cross-linking. It not only avoids the structural rigidity brought by chemical cross-linking, but also significantly enhances the material's tear and compression resistance.
[0046] (6) The present invention realizes simplification of the preparation process and cost control. Compared with existing composite materials, the preparation method does not require complicated doping or composite processes, simplifies the preparation process and reduces production costs, and has broad application and promotion prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0048] Figure 1 A roadmap for preparing nanoparticles in an embodiment of the present invention is shown;
[0049] Figure 2 The nanoparticle 1P used in Example 2 of the present invention 300-1 and other intermediates or raw materials;
[0050] Figure 3 The nanoparticle 1P used in Example 2 of the present invention 300 -1 and other intermediates or raw materials infrared spectra;
[0051] FIG. 4 is a diagram of I2959 and 1P in Examples 1 and 2 of the present invention. 300 -1 and 1P 300 -8 electron paramagnetic resonance (EPR) spectrum;
[0052] FIG. 5 shows G-1P in Examples 5-8 of the present invention and Comparative Example 1 300 -8, G-1P 300 -1, G-1P 500 -8, G-1P 500 Raman spectra of -1 and G-I2959 hydrogels;
[0053] FIG. 6 shows different hydrogels G-1P in Examples 5 and 6 of the present invention and Comparative Example 1 300 -8, G-1P 300 Comparison of stress-strain curves and stretch lengths of G-I2959 and G-1 at room temperature 25°C, -20°C, and -40°C; (a) is the stress-strain curve, (b) is the stretch length comparison diagram, from left to right 1-9 are hydrogels G-I2959 25°C, G-1P 300 -1 25℃、G-1P 300 -8 25℃, G-I2959 -20℃, G-1P 300 -1 -20℃、G-1P 300 -8 -20℃, G-I2959 -40℃, G-1P 300 -1 -40℃ and G-1P 300 -8 -40℃;
[0054] Figure 7 The hydrogel G-1P in Examples 5 and 6 of the present invention and Comparative Example 1 is different 300 -8, G-1P 300 -1 and G-I2959 at 25℃, -20℃, -40℃; (a) is the XRD pattern of hydrogel G-I2959 at 25℃, -20℃, -40℃, (b) is the XRD pattern of hydrogel G-1P 300 -1 at 25℃, -20℃, and -40℃, (c) is the XRD pattern of hydrogel G-1P 300 -8 XRD patterns at 25°C, -20°C, and -40°C;
[0055] FIG8 shows different hydrogels G-1P in Examples 5 and 6 of the present invention and Comparative Example 1 300 -8, G-1P 300 Surface temperature diagram of -1 and G-I2959 at 70°C and thermal conductivity diagram at 333 K-373 K; (a) is the surface temperature diagram at 70°C, and (b) is the thermal conductivity diagram at 333 K-373 K;
[0056] Fig. 9 The fluorescence spectra of the nanoparticles prepared in the examples and comparative examples of the present invention in aqueous solution, the fluorescence spectra of different hydrogels and the fluorescence photos under ultraviolet light; wherein (a)-(c) are the fluorescence spectra of nanoparticles I2959, 1P 300 -1 and 1P 300 -8 in aqueous solution, (d) G-I2959, G-1P 300 -1, G-1P 300 -8, fluorescence spectra of G-AIBN and G-APS hydrogels and fluorescence photos under UV light. DETAILED DESCRIPTION
[0057] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0058] Tetramethylammonium hydroxide (AR), tetraethyl orthosilicate (AR), allyl bromide (99%), 18-crown-6 (AR), boron trifluoride ether, platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane (2% xylene solution), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (I2959, ≥98%), and epibromohydrin (BCH, AR) were purchased from Aladdin Reagent Co., Ltd.; dimethylchlorosilane (98%) was purchased from Anage Reagent Co., Ltd.; polyethylene glycol (Mn=300, 500) was purchased from Sinopharm Chemical Reagent; silsesquioxane (POSS) was prepared by hydrolysis of tetraethyl orthosilicate in an alkaline environment of tetramethylammonium hydroxide; azobisisobutyronitrile (AIBN) was purchased from Aladdin Reagent Co., Ltd.; and ammonium persulfate (APS) was purchased from Komiou Reagent Co., Ltd.
[0059] Example 1
[0060] The synthesis of nanoparticles for modifying acrylamide hydrogels is mainly divided into two steps. The first step is the synthesis of PEG-modified POSS (POSS-PEG), and the second step is the synthesis of nanoparticles that give hydrogels high toughness, fluorescence and thermal insulation: I2959 grafted POSS-PEG. Specifically, the following steps are included:
[0061] 1. Preparation of I2959-Br:
[0062] Take 4.48 g of I2959 and dissolve it in 100 mL of anhydrous ethanol. Stir until it is completely dissolved. Then heat the solution to 55 °C and stabilize it. Then add 4.00 mL of boron trifluoride etherate as a catalyst to the solution twice. Then slowly add 2.74 g of epibromopropane (BCH) dropwise. The reaction lasts for 2 h. The unreacted BCH and solvent ethanol are removed by rotary evaporation to obtain 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone (I2959-Br).
[0063] 2. Preparation of POSS-PEG:
[0064] Under nitrogen atmosphere, 2.00 g of POSS monomer was dissolved in 120 mL of anhydrous toluene in a 200 mL round-bottom flask, and 5.20 g of Allyl-PEG was added. 300 -OH, then add 240 μL of platinum catalyst and stir at room temperature for 24 h. After the reaction is completed, add a small amount of CHCl3 to dilute, add a small amount of activated carbon, stir for 1 h, filter, remove the organic solvent by rotary evaporation, and place in a vacuum drying oven at 60 ° C for 24 h to obtain the product POSS-PEG 300 -OH.
[0065] 3. Preparation of nanoparticles:
[0066] Take POSS-PEG 300 -OH 7.38 g was dissolved in 50 mL acetone, nitrogen was passed in for protection, and then I2959-Br 5.78 g was added, stirred and dissolved, and then 1104 mg of potassium carbonate and 528 mg of 18-crown ether-6 were added, heated to 60 ° C, and refluxed for 12 h. After the reaction, 40 mL of water was added and extracted with an appropriate amount of ethyl acetate, and anhydrous sodium sulfate was added to the organic phase to remove water, and ethyl acetate was evaporated to obtain POSS-PEG-2959 nanoparticles, that is, nanoparticles 1P 300 -8.
[0067] 1P 300 -8, where P represents POSS monomer, 300 represents the molecular weight of polyethylene glycol modified with POSS monomer is 300, and 1,8 represents POSS-PEG 300 The molar ratio of -OH to I2959-Br in the reaction is 1:8.
[0068] Example 2
[0069] The difference from Example 1 is that in step (3), POSS-PEG 300The molar ratio of -OH to I2959-Br was 1:1, and 1P 300 -1 Same as above.
[0070] Example 3
[0071] The difference from Example 1 is that in step (3), POSS-PEG 500 The molar ratio of -OH to I2959-Br was 1:8, and 1P 500 -8Same as above.
[0072] Example 4
[0073] The difference from Example 1 is that in step (3), POSS-PEG 500 The molar ratio of -OH to I2959-Br was 1:1, and 1P 500 -1 Same as above.
[0074] Example 5
[0075] The preparation of the multifunctional hydrogel comprises the following steps:
[0076] Weigh 5 g of acrylamide and dissolve it in 5 g of water. After stirring for 1 h, add 20 μL of crosslinker polyethylene glycol diacrylate and 0.01 mmol of nanoparticles 1P of Example 1. 300 -8, continue stirring for 1 h to form a prepolymer solution, pour the prepolymer solution into a mold and cure it with a 370 nm UV lamp for 10 min to obtain G-1P 300 -8.
[0077] Example 6
[0078] The difference from Example 5 is that the nanoparticles 1P of Example 2 are used. 300 -1, then the hydrogel G-1P was prepared 300 -1.
[0079] Example 7
[0080] The difference from Example 5 is that the nanoparticle 1P of Example 3 is used. 500 -8, then the hydrogel G-1P was prepared 500 -8.
[0081] Example 8
[0082] The difference from Example 5 is that the nanoparticles 1P of Example 4 are used. 500 -1, then the hydrogel G-1P was prepared 500 -1.
[0083] Comparative Example 1
[0084] Different from Example 5, nanoparticles were not added, but I2959 was directly added to prepare the hydrogel G-I2959.
[0085] Comparative Example 2
[0086] Different from Example 5, nanoparticles were not added, but azobisisobutyronitrile (AIBN) was added to prepare the hydrogel G-AIBN.
[0087] Comparative Example 3
[0088] Different from Example 5, ammonium persulfate (APS) was added instead of nanoparticles to prepare the hydrogel G-APS.
[0089] Figure 2 From top to bottom, the nanoparticles 1P used in the present invention are 300 -1 and other intermediates or raw materials. The chemical structure of the target product was characterized and verified by nuclear magnetic resonance hydrogen spectrum (1H^NMR). The results showed that the characteristic peaks of each component were clearly visible, proving the successful synthesis of the material. In the spectrum, the Si-CH3 characteristic peak of silsesquioxane (POSS) appeared in the range of 0.0–0.5 ppm, the CH2-O-CH2 characteristic peak of the polyethylene glycol (PEG) chain segment appeared between 3.4–3.7 ppm, and the hydrogen on the aromatic ring of I2959 showed a typical signal in the range of 6.9–7.3 ppm. In addition, after I2959 was grafted at the end of PEG, the multiple peaks of CH2-OH appeared in the range of 3.8–4.2 ppm. During the reaction, the Si-H characteristic peak of POSS (4.5–5.0 ppm) and the double bond peak of C=C (5.8–6.2 ppm) disappeared, indicating that the addition reaction of Si-H and C=C had completely occurred, and the connection between POSS and PEG chain segments was successfully achieved. Comprehensive nuclear magnetic resonance hydrogen spectrum data further verified that POSS, PEG and I2959 formed a stable target product through chemical bonding, providing clear evidence support for the structure and function of the material of the present invention.
[0090] Figure 3 From top to bottom, the nanoparticles 1P used in the present invention are 300 -1 and other intermediates or raw materials. The infrared spectrum (FTIR) analysis results of the hydrogel material further verified the chemical structure and reaction of each component. In the spectrum, the characteristic absorption peak of the POSS part was first observed, located at about 1100 cm -1 The Si-O-Si stretching vibration peaks in the range of 1100 cm-1 and 1100 cm-2 show the integrity of the POSS structure. -1 Nearby, and at about 2800 cm-1 The absorption peak of CH stretching vibration was observed at 1700 cm, which indicates that the PEG segment was successfully integrated into the hydrogel system. In addition, the characteristic absorption peak of the carbonyl compound I2959 after grafting is also clearly visible. -1 Nearby, a typical C=O stretching vibration peak appeared, proving that the carbonyl functional group in I2959 was successfully integrated into the material. -1 At the junction of PEG and POSS and the CO-Si absorption peak of grafted I2959, the chemical bonding between POSS, PEG and I2959 was further verified. Before the reaction, the characteristic absorption peak of Si-H usually appeared at 2200 cm -1 The disappearance of this peak after the reaction indicates that Si-H reacts with C=C. By comparing the infrared spectra before and after the reaction, the disappearance of the Si-H absorption peak and the enhancement of the new CO and C=O absorption peaks prove the successful grafting reaction between POSS, PEG and I2959.
[0091] Figure 4 The electron paramagnetic resonance (EPR) spectra of I2959 and two POSS nano-photoinitiators. In the case of 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a spin trapping agent, an EPR spin trapping experiment was performed on the POSS nano-photoinitiator and I2959 aqueous solution to detect the generated free radicals. Figure 4 As shown, two DMPO radical adducts are generated in the I2959 solution, corresponding to the substituted benzoyl a value (the spacing of the spectrum line splitting produced when the unpaired electron spin dipole interacts with the magnetic core to produce the spectrum line splitting) of about 4.3 G and the alkyl a value of about 1.5 G, which is consistent with the initiator type I (that is, the photoinitiator molecule absorbs light energy and transitions to the excited singlet state, and then jumps to the excited triplet state through intersystem crossing. When it is in the excited triplet state or excited singlet state, the molecular structure is unstable, and the weak bonds therein will be homolytically split to produce primary active free radicals). This indirectly proves that both I2959 and POSS-based nanoparticles can produce the same carbonyl radicals for initiating the photocuring reaction of hydrogels.
[0092] Figure 5 shows G-I2959, G-1P 300 -1, G-1P 300 -8 、G-1P 500 -1 and G-1P 500 Raman spectra of -8 hydrogel. The hydrogel materials obtained by acrylamide initiated by I2959, POSS connected to one I2959 and connected to eight I2959 nanoparticles were characterized in detail by Raman spectroscopy, with a special focus on the 3250 cm -1 and 3500 cm -1The peak intensity changes at wavenumbers and 1650 cm -1 The evolution of nearby peaks is closely related to the hydrogen bonding and π-π interactions among the PEG segments, acrylamide and I2959.
[0093] At 3250 cm -1 and 3500 cm -1 At 3250 cm, they correspond to the characteristic peaks of amino (NH) and hydroxyl (OH) stretching vibrations. -1 The NH peak at 3500 cm -1 The OH peak at 3250 cm is relatively weak, indicating that the hydrogen bonding in the PEG segment is mainly concentrated between the amino group and other functional groups in the hydrogel. -1 The NH peak intensity at 3500 cm -1 The OH peak intensity at 100 nm also increases, which reflects the formation of more hydrogen bonding interactions. This phenomenon shows that the hydrogen bonding between PEG and acrylamide segments is enhanced by the grafting of I2959, and the hydrogen bonding network of the hydrogel is further complicated, which improves the toughness and stability of the material.
[0094] At 1650 cm -1 The enhancement of the C=O stretching vibration peak is closely related to the grafting of the carbonyl functional group in the I2959 molecule. -1 The C=O peak at 1650 cm is more significant, indicating that there is a strong hydrogen bond interaction between the carbonyl group in I2959 and the amino and hydroxyl groups in the hydrogel. -1 The C=O peak at 40° is further enhanced, indicating that more I2959 molecules are grafted into the hydrogel and the interaction of carbonyl functional groups is enhanced. At this time, the π-π interaction also plays a key role. The π-π stacking effect between the aromatic ring in I2959 and the benzene ring or other structural units with electron clouds in the hydrogel promotes the mutual attraction between molecules, thereby further enhancing the vibration peak intensity of C=O.
[0095] Figure 6 shows the stress-strain curves and elongation comparison diagrams of different hydrogels at 25°C, -20°C, and -40°C, where (a) is the stress-strain curve and (b) is the elongation comparison diagram. From left to right, 1-9 are hydrogels G-I2959 25°C, G-1P 300 -1 25℃、G-1P 300 -8 25℃, G-I2959 -20℃, G-1P 300-1 -20℃、G-1P 300 -8 -20℃, G-I2959 -40℃, G-1P 300 -1 -40℃ and G-1P 300 -8 Comparison of tensile length at -40℃.
[0096] according to Figure 6 The data analysis shows that the performance of acrylamide hydrogels initiated by I2959 in terms of stress and strain is significantly lower than that of hydrogels initiated by POSS-PEG-2959 nanoparticles. Taking 300 molecular weight PEG nanoparticles as an example, 1P 300 -1 and 1P 300 The stress performance of hydrogels initiated by POSS-PEG-2959 was significantly improved compared with that of hydrogels initiated by I2959, specifically, the stress increased from 0.25 kPa to 0.5 kPa, and the Young's modulus doubled. This change indicates that the introduction of nanoparticles, especially POSS-PEG-2959 nanoparticles, significantly enhanced the mechanical properties of hydrogels, which may be due to the role of nanoparticles in strengthening the skeleton in the hydrogel network and improving the rigidity of the material.
[0097] In addition, low temperature treatment has a significant effect on the stress-strain properties of the hydrogel. The hydrogels were frozen at -20°C and -40°C, and their stress-strain properties were measured after returning to room temperature. The results showed that the decrease in temperature significantly increased the elongation at break of the hydrogel. In particular, the lower the temperature, the higher the elongation at break of the hydrogel, which may be related to the reduced molecular mobility of the material under low temperature conditions, causing the hydrogel to undergo a greater degree of deformation (for example, the slippage of polymer chain segments or the rearrangement of water molecules). Nanoparticle-doped hydrogels showed similar rules, but compared with pure hydrogels, nanoparticle hydrogels showed higher strain properties, indicating that the introduction of nanoparticles enhances the flexibility and fracture resistance of the hydrogel at low temperatures.
[0098] From a mechanistic perspective, the introduction of POSS-PEG-2959 nanoparticles into hydrogels not only enhances their mechanical strength by providing additional mechanical support, but also maintains better structural stability and ductility in low-temperature environments through hydrogen bonding and physical entanglement with hydrogel segments. In addition, the increase in the elongation at break of hydrogels at low temperatures may be related to the enhanced hydrogen bonding interactions between molecules within the material, as well as the synergistic effect of the flexibility of the PEG segments and the rigidity of the nanoparticles. These factors work together to enable hydrogels containing nanoparticles to exhibit superior performance in terms of stress and strain properties.
[0099] Therefore, POSS-PEG-2959 nanoparticles not only significantly improved the stress and Young's modulus of the hydrogel, but also improved its toughness in low-temperature environments, broadening the application potential of the hydrogel under extreme conditions.
[0100] Figure 7 For G-I2959, G-1P 300 -1, G-1P 300 XRD patterns of G-I2959 hydrogel at 25°C, -20°C, and -40°C. According to the XRD pattern analysis, the change in the diffraction peak intensity ratio at 10° and 25° of the G-I2959 sample reflects the effect of low temperature on the crystal structure of the hydrogel. The diffraction peak at 10° may represent the low-temperature crystal structure of the hydrogel, while the diffraction peak at 25° represents the stable crystal structure at room temperature. As the temperature decreases, the intensity ratio of the 10° peak to the 25° peak decreases significantly, indicating that low temperature causes the interaction between I2959 molecules to weaken, thereby inducing relaxation of the crystal structure and causing its mechanical properties to decrease. This is consistent with the stress-strain properties of the hydrogel induced by I2959 - the stress and Young's modulus of the hydrogel are low, indicating that its mechanical properties are weak.
[0101] In G-1P 300 In the G-1P sample, the ratio of the diffraction peak intensity at 10° to 25° decreased, but the change was not as significant as that in the G-I2959 sample, indicating that PEG nanoparticles enhanced the structural stability of the hydrogel at low temperatures and reduced the change in the crystal structure. This is consistent with the improvement of its stress-strain properties. 300 -1-induced hydrogels exhibited higher values in stress and Young's modulus, indicating better mechanical properties.
[0102] G-1P 300 In the -8 sample, the diffraction peak intensity at 10° and 25° hardly changed, indicating that the hydrogel with more I2959 has higher structural stability and is less affected by low temperature. This is consistent with its advantages in stress-strain properties - the hydrogel has excellent strain properties, especially at low temperatures, showing higher elongation at break and better flexibility.
[0103] In general, the intensity changes of XRD data are closely related to the stress-strain properties of hydrogels. The introduction of PEG nanoparticles and POSS-PEG-2959 nanoparticles enhances the structural stability of hydrogels, especially at low temperatures, making the hydrogels exhibit better mechanical properties and thermal stability. These results indicate that the intermolecular interactions and the stability of the crystal structure are the key factors that determine the stress-strain properties of hydrogels.
[0104] FIG8 is a diagram of G-I2959, G-1P prepared in an embodiment of the present invention. 300 -1, G-1P300 -8 hydrogel surface temperature diagram at 70 °C and thermal conductivity diagram at 333 K-373 K; where (a) is the surface temperature diagram at 70 °C, and (b) is the thermal conductivity diagram at 333 K-373 K.
[0105] I2959 and 1P 300 -1 and 1P 300 -8 initiated polymerization hydrogel was placed on a 70°C heating plate, and the temperature changes on the upper and lower surfaces of the hydrogel were accurately measured using an infrared thermometer and a thermocouple (accurate to 0.1°C). According to the results of the hydrogel thermal insulation performance experiment, the surface temperature of the G-I2959 hydrogel quickly rose to 60°C within 4 minutes under 70°C heating conditions, which indicates that the hydrogel has a high thermal conductivity and is difficult to effectively block heat transfer. In contrast, G-1P 300 -1 and G-1P 300 Under the same heating conditions, the surface temperature of the -8 hydrogel only increased to 46°C and 41°C, respectively, and remained stable for 10 minutes. At room temperature to 100 degrees, its thermal conductivity averaged 0.0050, 0.0023, and 0.0028 (Wm -1 .K -1 ), which shows that they have better thermal insulation properties and can effectively slow down the transfer of heat.
[0106] Combined with the XRD and stress-strain property data mentioned above, G-I2959 hydrogel has a loose molecular structure and shows unstable crystal structure at low temperatures, so its thermal conductivity is strong and it is difficult to effectively insulate. 300 -1 and G-1P 300 -8 hydrogels are introduced with PEG segments and POSS-PEG-2959 nanoparticles. From the perspective of thermal insulation mechanism, the introduction of PEG and POSS not only improves the structural stability and mechanical properties of the hydrogels, but also effectively slows down the rate of heat conduction. Specifically, the flexibility and hydrophilicity of the PEG segments may help to form a more uniform molecular arrangement, thereby forming an effective thermal isolation channel in the hydrogel. The introduction of POSS-PEG-2959 nanoparticles may further reduce the transfer of heat through its rigid skeleton and hydrogen bonding, making the hydrogel exhibit lower thermal conductivity at high temperatures and enhancing its thermal insulation properties.
[0107] Fig. 9 The fluorescence spectra of the nanoparticles prepared in the examples and comparative examples of the present invention in aqueous solution, the fluorescence spectra of different hydrogels and the fluorescence photos under ultraviolet light; wherein (a)-(c) are the fluorescence spectra of nanoparticles I2959, 1P 300 -1 and 1P 300-8 in aqueous solution, (d) G-I2959, G-1P 300 -1, G-1P 300 -8, fluorescence spectra of G-AIBN and G-APS hydrogels and fluorescence photos under UV light.
[0108] The fluorescence properties of the hydrogel in the present invention do not come from the addition of an external fluorescent agent, but from the proton transfer mechanism of I2959 and the system. The experimental results show that I2959 itself does not have the ability to emit fluorescence, and no fluorescence phenomenon is observed when it is physically mixed with PEG or POSS. However, when I2959 is grafted onto POSS-PEG nanoparticles and excited by 365 nm ultraviolet light, the hydrogel can emit significant bright blue fluorescence. This shows that the fluorescence properties of I2959 are closely related to its molecular structure and proton transfer in the POSS-PEG system. Whether it is G-1P 300 -1 or G-1P 300 -8 hydrogels all showed obvious blue fluorescence, and with the increase of I2959 grafting amount, the fluorescence intensity gradually increased, showing the adjustability of fluorescence performance. However, the G-AIBN and G-APS hydrogels prepared by other initiators such as azobisisobutyronitrile (AIBN) and ammonium persulfate (APS) did not show fluorescence effect.
[0109] In summary, the present invention provides an innovative hydrogel material based on polyethylene glycol segment-modified silsesquioxane (POSS), which achieves a high degree of integration of thermal insulation, fluorescence properties and toughness through the design and optimization of nanoparticles. By combining the rigid skeleton of POSS with the flexible segment of PEG, the material exhibits excellent thermal insulation performance in the temperature range of 60°C to 100°C, and the thermal conductivity is as low as 0.0023 W / (m·K). By grafting the carbonyl compound I2959 at the end of the PEG chain and utilizing the transfer effect between it and the protons of the system, the material exhibits a fluorescence emission of 425 nm under 365 nm ultraviolet light excitation. In addition, the synergistic effect between the flexible PEG segment and the rigid POSS further enhances the toughness of the hydrogel through hydrogen bonding and physical entanglement. The present invention not only effectively solves the problems of weak mechanical properties, poor thermal stability and single function of traditional hydrogels, but also provides a new solution for multifunctional hydrogel materials in thermal insulation protection, fluorescence sensing, flexible devices and other high-performance application fields. This technology has broad industrialization prospects and practical application value.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of a multifunctional hydrogel in the fields of thermal insulation protection, fluorescence sensing, and low-temperature flexible devices. The preparation method of the multifunctional hydrogel comprises the following steps: acrylamide, water, a cross-linking agent and nanoparticles are mixed and stirred to form a prepolymer solution, and then a multifunctional hydrogel is obtained by ultraviolet light curing; Under ultraviolet light excitation, the multifunctional hydrogel emits bright blue fluorescence with a wavelength of 350-450 nm; the ultraviolet light excitation wavelength is 360-370 nm; When heated at 70°C, the surface temperature of the multifunctional hydrogel only rises to 40°C to 50°C and can remain stable within 10 minutes; The nanoparticles are composed of silsesquioxane and polyethylene glycol chain segments, and the ends of the polyethylene glycol chain segments are grafted with 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
2. The use according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 200-3500.
3. The use according to claim 1, characterized in that: The following steps are involved: (1) Using silsesquioxane and propylene polyethylene glycol hydroxyl groups as raw materials, adding a catalyst to react, and obtaining a polyethylene glycol-modified silsesquioxane product; (2) The polyethylene glycol-modified silsesquioxane product is mixed with 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone, potassium carbonate and crown ether are added, and the mixture is reacted and extracted to obtain nanoparticles.
4. The use according to claim 3, characterized in that In step (1), the ratio of silsesquioxane, propylene polyethylene glycol hydroxyl group and catalyst is (1-2 g): (5-6 g): (200-300 μL); the catalyst is a platinum catalyst, and the platinum catalyst is platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, and its concentration is 1-3% xylene solution; when the catalyst is added to the reaction, stirring is carried out at room temperature for 12-36 hours; Alternatively, in step (2), the preparation method of 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone is: dissolving 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone in an organic solvent, heating, adding a catalyst and epibromopropane to the organic solvent for reaction, and removing unreacted epibromopropane and the organic solvent to obtain 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone; The catalyst is boron trifluoride etherate; the heating temperature is 50-60°C; the reaction time is 1-5 h; the ratio of the added amounts of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, organic solvent, catalyst, and epibromopropane is (4-5 g):100 mL:(4-8 mL):(2-3 g).
5. The use according to claim 3, characterized in that: In step (2), The ratio of 1-(4-(2-(3-bromo-2-hydroxypropoxy)ethoxy)phenyl)-2-methylpropiophenone, potassium carbonate and crown ether is (5-6 g):(1000-1200 mg):(500-600 mg); In step (2), the reaction temperature is 50-70°C and the reaction time is 10-14 h.